Concept mapping as a strategy to scaffold concept literacy in accounting for extended programmes - Immelman, S.; Carstens, A.; Smith, S.; Masenge, A. (South African Journal of Higher Education, 2020)
While great strides have been made to improve accessibility to higher education in South Africa, successful completion of bachelor's degrees within the prescribed time remains a challenge.  Research suggests that a lack of conceptual understanding by students might be at the heart of the problem. This study, which is grounded in Ausubel's Assimilation Theory as applied by Joseph Novak and his colleagues, investigates the value of concept mapping as a scaffolding technique to improve conceptual understanding. The research involved a quasi-experiment with a test and a control group. It was hypothesised that accounting students in an extended programme who had been introduced to the concept mapping technique would demonstrate an improved grasp of accounting concepts, indicated by an improvement in their marks when composing an explanatory paragraph of accounting concepts after a teaching intervention. However, the post-intervention marks of the test group showed no improvement, and therefore no proof can be offered to support the claim that concept mapping improves conceptual understanding. Pre-and post-intervention questionnaires were used to collect data on confounding variables and also to assess student experiences of concept mapping. An analysis of student experiences indicated enthusiasm for the technique. Limitations of the study included the absence of a pilot study and insufficient time to become familiar with concept mapping. An unforeseen constraint on the study was low student participation.